Offshore floating solar with electrofuels for refuelling small ferries: A techno-economic-environmental study - Kaur, Nisha; Hariram, Nediyirippil Prakasan; Mekha, K. B.; Mohd Rusllim, Mohamed; Priya, S. Shanmuga; Sudhakar, Kumarasamy (Elsevier Ltd, 2025)
The decarbonization of maritime shipping presents a critical challenge in achieving global climate targets, necessitating a rapid transition from fossil fuels to sustainable alternatives. Offshore renewable energy with electro-fuels for ship refuelling addresses the critical global challenge of decarbonizing maritime shipping, which currently contributes approximately 2–3 % of global greenhouse gas emissions. Through a techno-economic modelling framework and case analysis of Redang Island, Malaysia, this research evaluates the technical feasibility, cost dynamics, and environmental aspects of producing hydrogen-based e-fuels for green ship refuelling through offshore floating PV. The analysis considers local solar resources, system design, hydrogen storage, and the logistical requirements for ship refuelling, alongside economic parameters such as capital and operational expenditures, levelized cost of hydrogen, and potential carbon emission reductions. Results indicate that over its lifetime, the 20 MW offshore floating solar system is expected to produce approximately 637,619 MWh of solar energy and 12,892 tonnes of hydrogen at an estimated total cost of MYR 175.84 million, resulting in a levelized cost of electricity (LCOE) of MYR 0.276/kWh and a levelized cost of hydrogen (LCOH) of MYR 13.64/kg. Compared to conventional fuels, e-hydrogen exhibits greater techno-economic-environmental benefits even for short-distance cruise ships due to the higher energy density of the fuel. Integrating offshore floating solar with hydrogen production can provide a sustainable and scalable pathway for decarbonising maritime transport in Malaysia, supporting national renewable energy targets, and contributing to the global transition towards netzero emissions. The future scope includes the importance of international standards for maritime e-fuel, adaptation at major bunkering ports, a carbon pricing mechanism, and policy support to enable operation at coastal, offshore, and Island locations.